Two‐year protocol biopsy after kidney transplantation in clinically stable recipients – a retrospective study - Chen, Chien‐Chia; Lin, Wei‐Chou; Lee, Chih‐Yuan; Yang, Ching‐Yao; Tsai, Meng‐Kun (Transplant international, 2021)
Summary The idea of protocol biopsy is to detect subclinical pathologies, including rejection, recurrent disease, or infection for early intervention and adjustment of immunosuppressants. Nevertheless, it is not adopted by most clinicians because of its low yield rate and uncertain long‐term benefits. This retrospective study evaluated the impact of protocol biopsy on renal function and allograft survival. A two‐year protocol biopsy was proposed for 190 stable patients; 68 of them accepted [protocol biopsy (PB) group], while 122 did not [nonprotocol biopsy (NPB) group]. The rejection diagnosis was made in 13 patients by protocol biopsy, and 11 of them had borderline rejection. In the following 5 years, graft survival was better in the PB group than in the NPB group (P = 0.0143). A total of 4 and 17 patients in the PB and NPB groups, respectively, had rejection events proven by indication biopsy. Renal function was better preserved in the PB group than in the NPB group (P = 0.0107) for patients with rejection events. Nevertheless, the survival benefit disappeared by a longer follow‐up period (12‐year, P = 0.2886). In conclusion, 2‐year protocol biopsy detects subclinical pathological changes in rejection and preserves renal function by early intervention so as to prolong graft survival within 5 years.